N-Butylparaben exposure through gestation and lactation impairs spermatogenesis and steroidogenesis causing reduced fertility in the F1 generation male rats. (January 2020) - Maske, Priyanka; Dighe, Vikas; Mote, Chandrashekhar; Vanage, Geeta
Abstract: Parabens are class of preservatives used in vast majority of commercial products, and a potential Endocrine Disrupting Chemical (EDC). The present study was undertaken to delineate the effects of n-butylparaben on F1 male progeny exposed maternally through gestation and lactation via subcutaneous route. The F0 dams were given subcutaneous injections of n-butylparaben from gestation day (GD) 6 to postnatal day (PND) 21 with doses of 10, 100, 1000 mg/kg Bw/day in corn oil. The F1 male rats were monitored for pubertal development and sexual maturation; these were sacrificed on PND 30, 45 and 75. On PND 75, these F1 male rats were subjected for fertility assessment with unexposed female rats. A delayed testicular descent at 100 and 1000 mg/kg Bw dose and delayed preputial separation at 10 mg/kg Bw dose was observed in exposed F1 male rats. Decreased sperm count, motility and Daily Sperm Production was observed at 100 mg/kg Bw dose at PND 75. Interestingly, the sperm transit time in the epididymis was accelerated at this dose. Significant perturbed testicular expression of steroid receptors (ERα and β, AR), INSL3 and StAR genes with increased T and LH levels indicates direct effect on spermatogenesis and steroidogenesis. These F1 generation adult rats were sub-fertile with increased (%) pre- and post-implantation loss at 100 and 1000 mg/kg Bw/day dose. This is the first report on n-butylparaben highlighting the involvement of testicular leydig cells with accelerated sperm transit time leading to reduced fertility in the maternally exposed F1 male rats through estrogenic/anti-androgenic action. Graphical abstract: Image 1077 Highlights : n-butylparaben exposure resulted in delayed age at testicular descent and preputial separation. Decreased sperm count, motility, DSP and sperm transit time of F1 male rats at PND 75. n-butylparaben perturbed the steroid hormone homeostasis in the perinatally exposed F1 male rats. The F1 male rats exposed to n-butylparaben were sub-fertile with increased (%) pre- and post-implantation loss. Perturbed testicular expression of SR's and its related genes in n-butylparaben exposed F1 male rats.